Tourism and the environment: Ecotourism as a sustainable tourism development approach towards the enhancement of environment - Ahmad, Mohamad Zaki; Ibrahim, Johan Afendi (2004)
As tourism is now one of the world's leading industries,the environment is taking center stage in tourism development. The environment is the core of the tourism product since profitability in tourism depends on maintaining the attractiveness of the destination people want to see and experience. Not only a powerful economic force, tourism is a factor in the physical environment as well. Tourism can generate both positive and negative environmental impacts, depending on how well development is planned and controlled. Tourism has the power to enhance the environment but at the same time it has the power to desiroy,too. Realizing of the negative impacts that tourism might bring, efforts have been taken to make sure that tourism can be sustained over a long period of time. In this context, sustainable tourism development is recognized as the most practical approach to be adopted. This paper discusses the concept of tourism by highlighting definition of tourism, background and nature of tourism, industry, its components and factors influencing participation in tourism related activities. Then, discussion focuses on tourism and the environment before further discussing the concept of sustainable tourism development by highlighting the importance and significance of 'ecotourism '. The paper concludes by recommending a possible allocation of responsibility' for all in the industry as well as several 'ways' that organizations in tourism can do to support sustainable tourism.